ChemInform Abstract: Highly Active Nano‐MgO Catalyzed, Mild, and Efficient Synthesis of Amidines via Electrophilic Activation of Amides. Issue 46 (24th October 2013) - Das, Vijay Kumar; Thakur, Ashim Jyoti
Abstract The reusable and cheaper catalyst is successfully applied to the title synthesis.